1997
DOI: 10.1038/385653a0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the C. elegans cell-death regulators CED-9 and CED-4

Abstract: Programmed cell death (apoptosis) is an evolutionarily conserved process used by multicellular organisms to eliminate cells that are not needed or are potentially detrimental to the organism. Members of the Bcl-2 family of mammalian proteins are intimately involved in the regulation of apoptosis, but, their precise mechanism of action remains unresolved. In Caenorhabditis elegans, the Bcl-2 homologue CED-9 prevents cell death by antagonizing the death-promoting activities of CED-3, a member of the Caspase fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
154
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(165 citation statements)
references
References 26 publications
10
154
1
Order By: Relevance
“…29 While we cannot eliminate the possibility that the CED-4/CED-9 complex known to be associated with the mitochondrial membrane in the worm exists in a different oligomeric form to that described here for the E. coli-derived complex, our biochemical data for different complexes, including mutants, are consistent with the features of the protein complex characterised previously. 5,6,[8][9][10]12,15 For example, we have shown that the formation of the complex is not dependent on the presence of the CARD of CED-4, consistent with the requirement that it be free to recruit CED-3 to a trimolecular complex of CED-3/CED-4/CED-9. 7 This result agrees with other studies using yeast two-hybrid assays showing a strong interaction between CED-9 and CED-4 with its CARD deleted.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…29 While we cannot eliminate the possibility that the CED-4/CED-9 complex known to be associated with the mitochondrial membrane in the worm exists in a different oligomeric form to that described here for the E. coli-derived complex, our biochemical data for different complexes, including mutants, are consistent with the features of the protein complex characterised previously. 5,6,[8][9][10]12,15 For example, we have shown that the formation of the complex is not dependent on the presence of the CARD of CED-4, consistent with the requirement that it be free to recruit CED-3 to a trimolecular complex of CED-3/CED-4/CED-9. 7 This result agrees with other studies using yeast two-hybrid assays showing a strong interaction between CED-9 and CED-4 with its CARD deleted.…”
Section: Discussionsupporting
confidence: 78%
“…5,12,13 These have been complemented by mutational analysis of both CED-4 and CED-9. 9,10,14 Similarly, numerous studies have demonstrated the interaction between CED-9 and EGL-1, and release and/or redistribution of CED-4 from the mitochondria. 3,12,[14][15][16] Recently, three-dimensional structures were determined for the Bcl-2 homology region of CED-9 alone, 16 and in complex with an EGL-1 fragment encompassing its BH3 domain, 14 confirming the structural similarity with the mammalian Bcl-2 prosurvival family members 17,18 and their mode of engagement with BH3 domains.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apaf-1 possesses a CARD domain which interacts with a similar domain within the N-terminus of pro-caspase-9 (and pro-caspase-2?). This leads to the formation of a tri-molecular complex containing Bcl-2/Bcl-X L , Apaf-1, and pro-caspase-9, in analogy to the trimolecular complex formed in C. elegans by CED9, CED4 and the pro-caspase CED3 (Spector et al, 1997). This trimolecular complex has been nick-named the`apoptosome' and may explain most features of cell death regulation in C. elegans (Hengartner, 1997).…”
Section: Indirect Interactions Between Bcl-2 and Caspasesmentioning
confidence: 99%
“…Similar to CED-4, and most probably to proCED-3, the anti-apoptotic CED-9 protein is present in many cells at this stage (Chen et al, 2000). CED-9 localizes to the outer mitochondrial membrane, and it is through the physical interaction between CED-9 and an asymmetric dimer of CED-4 that the ability of CED-4 to form an active apoptosome and to mediate proCED-3 activation is blocked (Spector et al, 1997;Chinnaiyan et al, 1997b;Wu et al, 1997b;Chen et al, 2000;Yan et al, 2005). In the 113 cells that are programed to die, this block is released by the EGL-1 protein.…”
mentioning
confidence: 99%